Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/sym11050623
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Attribute Decision Making Based on Probabilistic Neutrosophic Hesitant Fuzzy Choquet Aggregation Operators

Abstract: Take the third-party logistics providers (3PLs) as an example, according to the characteristics of correlation between attributes in multi-attribute decision-making, two Choquet aggregation operators adoping probabilistic neutrosophic hesitation fuzzy elements (PNHFEs) are proposed to cope with the situations of correlation among criterions. This measure not only provides support for the correlation phenomenon between internal attributes, but also fully concerns the incidental uncertainty of the external space… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…Hence, Equations (25), (31), and (35) are used in comparison to determine their relationship with α j of Equation (26). By the same observation, it is found that Equations (27), (32), and (36) are related to β j of Equation (28).…”
Section: Further Discussion For Aggregation Operatorsmentioning
confidence: 84%
See 2 more Smart Citations
“…Hence, Equations (25), (31), and (35) are used in comparison to determine their relationship with α j of Equation (26). By the same observation, it is found that Equations (27), (32), and (36) are related to β j of Equation (28).…”
Section: Further Discussion For Aggregation Operatorsmentioning
confidence: 84%
“…In Equations (25) and (27), the most natural approach f ðxÞ = x is applied by us. Meanwhile, in Equations (31) and (32), Ye and Fu [7] used f ðxÞ = tan ðπx/4Þ, and in Equations (35) and (36) For a similarity measure, say Sim, Simð0Þ = 1, and Simð1Þ = 0 are ideal, such as in Equations (25), (27), (31), and (32) and then abstractly expressed in Equations (33) and (34), researchers use 1 − ∑ m j=1 w j f ðα j Þ or 1 − ∑ m j=1 w j f ðβ j Þ.…”
Section: Further Discussion For Aggregation Operatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the future, we will extend probabilistic to other fuzzy sets. For instance, dual hesitant sets [39], linguistic dual hesitant fuzzy sets [40], Neutrosophic Hesitant Fuzzy sets [41], Mixed-discrete Z-numbers [42], Pythagorean fuzzy Hamacher Prioritized operators [43], dual hesitant Pythagorean fuzzy sets [44], generalized Dice similarity measures of PFS [45], Pythagorean Fuzzy Hamacher Power Aggregation Operators [46], etc.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the studies in the area of neutrosophic theory, it can be underline the fact that the neutrosophic theory and its derivates has been extensively applied in the last two decades various economic and social fields such as-decision making [2][3][4][5][6][7][8][9][10][11][12][13], supply chain management [14], best product selection [15], management [16] forecasting [17], sentiment analysis [18,19] and so forth.…”
Section: Literature Reviewmentioning
confidence: 99%